The Contribution of The Realization of Agricultural Product Industry Investment to Gross Domestic Product of Agricultural and Employment in Indonesia - Ugi Sugiharto; Pudji Astuty; Sugiyanto , Sugiyanto (PT. ALHAFI BERKAH INDONESIA, 2025)
The agricultural sector plays a crucial role in Indonesia's economy, contributing significantly to the Gross Domestic Product (GDP) and providing employment opportunities for a large portion of the population. Recent trends indicate an increase in investments in the agricultural product industry, which raises important questions about its potential impact on economic growth and job creation. Understanding this relationship is vital for policymakers aiming to enhance the sector's contributions to overall economic development.. This research aims to investigate the contribution of agricultural product industry investment to the Gross Domestic Product (GDP) of the agricultural sector and employment levels. To achieve this, the study employs the Error Correction Model (ECM) for data analysis, enabling a thorough examination of both short-term and long-term relationships between the variables. The results reveal that the realization of agricultural industry investment has a significant and positive impact on agricultural GDP and employment opportunities. These findings underscore the potential of agricultural investment as a vital strategy for stimulating economic growth and addressing unemployment in the sector.